Cytokine profiling reveals HLA-linked Th2 and Th17 driven immune activation in pemphigus vulgaris patients and genetically susceptible healthy controls - Schwartz, Rebekah R.; Seiffert-Sinha, Kristina; Sinha, Animesh A. (Frontiers in Immunology, 2024)
IntroductionCytokines and chemokines direct the inflammatory response and may serve as markers of immune dysregulation in Pemphigus vulgaris (PV), an autoimmune blistering skin disorder. Previous studies on limited numbers of patients and cytokine profiles in PV have produced equivocal results regarding the role these mediators play in disease.MethodsIn this study, we interrogated serum samples from 116 PV patients and 29 healthy controls by multiplexed bead array assays across a comprehensive set of cytokines and chemokines covering several functional categories, including IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-9, IL-10, IL-12, IL-13, IL-15, IL-17, IL-21, IL-22, IL-23, TNFα, IFNγ, MCP-1, and Eotaxin.ResultsWe found that patients with PV generally display an activated cytokine and chemokine immune response compared to controls, but also show remarkable interindividual heterogeneity in terms of cytokine levels, with a limited activation of different T helper cell pathways in different patients. Surprisingly, we also found that healthy individuals that carry the PV susceptibility alleles HLA DR4 (DRB1*0402) and/or DR6 (DQB1*0503) (HLA-matched controls) show an upregulation of cytokine and chemokine levels that are on par with those seen in PV patients for certain pro-inflammatory, Th2, and Th17 mediators and IL-8, while healthy controls that did not carry the PV susceptibility alleles (HLA-unmatched controls) express significantly lower levels of these cytokines and chemokines.DiscussionOur data suggest the existence of a limited immune activation linked to the presence of key PV associated HLA alleles regardless of disease status. Interestingly, the cytokines IL-10 and IL-15 were found to be significantly downregulated in the HLA-matched control group, suggesting the presence of a possible counter-regulatory function in genetically susceptible but disease-free individuals.